2016
DOI: 10.1016/j.eurpsy.2016.01.2272
|View full text |Cite
|
Sign up to set email alerts
|

Online mindfulness as therapy for fibromyalgia patients

Abstract: IntroductionFibromyalgia is a chronic disease. This diagnosis has been controversial in scientific society. However, there is one fact: there are women who feel not only uncontrollable and non-specific body pain, but also psychological symptoms.ObjectiveTo compare the efficacy of online sessions versus in onsite sessions. To demonstrate that online mindfulness sessions could help to reduce pain in patients with a diagnosis of fibromialgya.MethodA website created to give education and advice to women with fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Online administration of therapeutic programs are believed to provide greater access to users, cost less, and be more inviting to the millennial generation (Maples & Han, ; Muñoz et al, ). Online mindfulness approaches are a recent development, but preliminary findings demonstrated that they are effective in mitigating a host of clinical concerns, including anxiety, stress, depression, psychological distress, and the pain associated with fibromyalgia (Cavanagh et al, ; Garrido‐Torres et al, ; Kemper, ; Krusche et al, ). These findings show that online mindfulness programs hold considerable promise for clinical applications and have the potential of bypassing some of the limitations of face‐to‐face administrations, alleviating the stress placed on college counseling centers.…”
mentioning
confidence: 99%
“…Online administration of therapeutic programs are believed to provide greater access to users, cost less, and be more inviting to the millennial generation (Maples & Han, ; Muñoz et al, ). Online mindfulness approaches are a recent development, but preliminary findings demonstrated that they are effective in mitigating a host of clinical concerns, including anxiety, stress, depression, psychological distress, and the pain associated with fibromyalgia (Cavanagh et al, ; Garrido‐Torres et al, ; Kemper, ; Krusche et al, ). These findings show that online mindfulness programs hold considerable promise for clinical applications and have the potential of bypassing some of the limitations of face‐to‐face administrations, alleviating the stress placed on college counseling centers.…”
mentioning
confidence: 99%
“…Traveling to in-person classes is a burden on those dealing with cancer (Kinner et al 2018 ; Smith et al 2005 ). When compared with an in-person mindfulness-based intervention, online MBPs are frequently determined to be similarly effective (Gardner-Nix et al 2008 ; Garrido-Torres et al 2016 ). Both cancer and pain populations report improvements in anxiety, depression, and pain intensity (Cillessen et al 2019 ; Dowd et al 2015 ; Messer et al 2019 ), where cancer patients report additional improvements in fear of cancer recurrence, sleep, and fatigue (Cillessen et al 2019 ) and chronic pain patients reporting decreases in total pain interference, pain catastrophizing, and increases in pain acceptance (Dowd et al 2015 ; Hearn and Finlay 2018 ).…”
mentioning
confidence: 99%